Antibiotic prophylaxis in dentistry - B. D'Orto; Lara Ceresoli; Serena Ferri; Costanza Ferraro; M. Nagni (Publymed, 2020)
The aim of the present narrative review was to summarize the main indications of antibiotic prophylaxis in dentistry.